2023
DOI: 10.1111/1759-7714.14840
|View full text |Cite|
|
Sign up to set email alerts
|

Segmentectomy versus lobectomy for small‐sized pure solid non–small cell lung cancer

Abstract: Background: Segmentectomy has been recommended for ground glass opacity (GGO)-dominant small-sized non-small cell lung cancer (NSCLC) or those with GGO component. Pure solid NSCLC is a special sub-type and has an inferior prognosis. Whether segmentectomy could achieve comparable long-term outcomes with lobectomy for pure solid small-sized NSCLC remained controversial. This study aimed to compare the prognosis of segmentectomy and lobectomy for pure solid NSCLC. Methods: NSCLC patients with a pure solid nodule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
1
1
Order By: Relevance
“…However, among patients with CTR ≥ 0.7, sublobar resection was associated with poorer outcomes than lobar resection, which is consistent with previous studies [ 19 , 20 ]. In contrast, our results were inconsistent with those of Li et al [ 21 ], who showed that sublobar resection could achieve oncological outcomes comparable to lobar resection for pure solid small-sized NSCLC. This contradiction may be caused by our cases precluding lymph node metastasis, while the lobar resection group had a higher rate of lymph node metastasis than the sublobar resection arm, acquiring more positive events in the lobar resection group.…”
Section: Discussioncontrasting
confidence: 99%
“…However, among patients with CTR ≥ 0.7, sublobar resection was associated with poorer outcomes than lobar resection, which is consistent with previous studies [ 19 , 20 ]. In contrast, our results were inconsistent with those of Li et al [ 21 ], who showed that sublobar resection could achieve oncological outcomes comparable to lobar resection for pure solid small-sized NSCLC. This contradiction may be caused by our cases precluding lymph node metastasis, while the lobar resection group had a higher rate of lymph node metastasis than the sublobar resection arm, acquiring more positive events in the lobar resection group.…”
Section: Discussioncontrasting
confidence: 99%
“…The main treatment for small lung nodules is surgery, which includes lobectomy, segmentectomy and wedge resection [18,19]. Recently, segmentectomy has been regarded as a common type of surgery [20,21]. In this study, we demonstrated the use of a true lung segmentectomy technique, lobar split cone-shaped subsegmentectomy.…”
Section: Discussionmentioning
confidence: 89%